Modelling the response of net primary productivity (NPP) of boreal forest ecosystems to changes in climate and fire disturbance regimes - Peng, Changhui; Apps, Michael J (Ecological Modelling, 1999)

simulating carbon dynamics along the Boreal Forest Transect Case Study (BFTCS) in central Canada: 2. Sensitivity to climate change - Peng, Changhui; Apps, Michael J. (Global Biogeochemical Cycles, 1998)
The effects of climate change and doubling atmospheric CO 2 on carbon dynamics of the boreal forest in the area of the Boreal Forest Transect Case Study in central Canada were investigated using the process‐based plant‐soil model CENTURY 4.0. The results presented here suggest that (1) across the transect climate change would result in increased total carbon in vegetation biomass but decreased overall carbon in soil; (2) increased atmospheric CO 2 concentration under current climatic patterns would result in increased total carbon in vegetation and in soil organic matter; and (3) combined climate change and elevated CO 2 would increase both net primary productivity and decomposition rates relative to the current climate condition, but their combined action would be a reduction of soil carbon losses relative to those due to climate change alone. The interactive effects of climate change and elevated CO 2 , however, are not a simple additive combination of the individual responses. The responses to climate change and elevated CO 2 vary across the climate gradient from southern to northern sites on the transect. The present simulations indicate that the northern sites are more sensitive to climate change than the southern sites are, but these simulations do not consider likely changes in the disturbance regime or changes in forest species distribution.

Contribution of China to the global carbon cycle since the last glacial maximum - Peng, Changhui; Apps, Michael J. (Tellus B: Chemical and Physical Meteorology, 1997)

Modelling the spatial pattern of net primary productivity in Chinese forests - Jiang, Hong; Apps, Michael J; Zhang, Yanli; Peng, Changhui; Woodard, Paul M (Ecological Modelling, 1999)

Simulating carbon dynamics along the Boreal Forest Transect Case Study (BFTCS) in central Canada: 1. Model testing - Peng, Changhui; Apps, Michael J.; Price, David T.; Nalder, Ian A.; Halliwell, David H. (Global Biogeochemical Cycles, 1998)
CENTURY 4.0, a simulation model of carbon and nitrogen dynamics of terrestrial ecosystems based on the relationships between climate, soil texture, plant productivity, decomposition and human management, was tested against observed data along the boreal forest transect case study (BFTCS) in central Canada. The results show that the simulated average aboveground biomass and net N mineralization were consistent with observed data. The modeled estimates for soil carbon were consistent with those from regional‐scale empirical regression models. High correlation ( R 2 = 0.92) with data was obtained for the simulation of soil carbon dynamics of the boreal forest, but the model overestimated soil carbon (O–20 cm) by 2–8% for fine‐textured soil and underestimated soil carbon by 5–18% for sandy soil. The effects of climatic variation on temporal changes in biomass and soil carbon storage over the past century were found to be very different for southern and northern sites but relatively insensitive to site‐specific soil texture. The main discrepancies between observed data and CENTURY 4.0 results are associated with the effects of soil texture and an inadequate representation of fire disturbance on C dynamics of boreal forests. Further improvements, particularly in the representation of disturbance regimes and in the simulation of slow pool C dynamics, are suggested to enhance its predictive capability.

Modelling the net primary productivity of temperate forest ecosystems in China with a GAP model - Jiang, Hong; Peng, Changhui; Apps, Michael J; Zhang, Yanli; Woodard, Paul M; Wang, Zhiming (Ecological Modelling, 1999)